Skiing - Gifford, Clive (New York : PowerKids Press, 2011)
Reviews the history of skiing, discusses how to get started in the sport, examines gear and equipment, features photographs and descriptions of various skiing moves and techniques, provides safety tips, and looks at skiing styles and competitions.
Includes bibliographical references (p. 31) and index.
6.9
5-8
5-8
Keywords: Skis and skiing -- Juvenile literature; Skis and skiing; Skis and Skiing